2020
DOI: 10.1111/jcmm.14996
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PLK4 might enhance the anti‐tumour effect of bortezomib on glioblastoma via PTEN/PI3K/AKT/mTOR signalling pathway

Abstract: GBM) is one of the most common aggressive cancers that occurs in the adult brain, and the survival period after initial diagnosis is only 12-15 months. 1 GBM accounts for nearly 70% of all adult brain tumours. 2 Effective treatment for GBM, which is characterized by rapid proliferation ability and highly infiltrative growth, is still lacking. 3 Bortezomib is a selective and reversible proteasome inhibitor that was first developed for the treatment of inflammation and cachexia in the late 90 seconds. 4 Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…In addition, the anti-tumor effect of bortezomib was enhanced after Plk4 knockdown in three (LN-18, A172 and LN-229) GBM cell lines and xenograft experiments. Further investigations indicate that this effect may be mediated by the PTEN/PI3K/AKT/mTOR signaling pathway (170). Thus, these findings indicated that Plk4 is a promising therapeutic target for GBM.…”
Section: Plk4 and Nervous System Tumorsmentioning
confidence: 83%
“…In addition, the anti-tumor effect of bortezomib was enhanced after Plk4 knockdown in three (LN-18, A172 and LN-229) GBM cell lines and xenograft experiments. Further investigations indicate that this effect may be mediated by the PTEN/PI3K/AKT/mTOR signaling pathway (170). Thus, these findings indicated that Plk4 is a promising therapeutic target for GBM.…”
Section: Plk4 and Nervous System Tumorsmentioning
confidence: 83%
“…Nowadays, a new generation of mTOR inhibitors is under investigation that acts as Adenosine Triphosphate (ATP) analogues in competition with ATP to bind to the mTOR protein. Interestingly, unlike rapamycin and its analogues, this generation of mTOR inhibitors is able to inhibit both the mTORC1 and mTORC2 complexes [69].…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of PLK4 has been studied in several cancers (37)(38)(39)(40), to narrow our scope for this review, we have focused on epithelial cancers. Although PLK4 has not been found to be commonly mutated in human neoplasms, due to its frequently aberrant expression and its importance in regulating the centriole and centrosome duplication cycle and links to many other crucial proteins, researchers have focused on PLK4 as a potential cancer biomarker.…”
Section: Plk4 In Epithelial Cancersmentioning
confidence: 99%